Labour brokerage in China today: Formal and informal dimensions - Li Minghuan (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2004)
Based on a three-year fieldwork in China's Fujian Province (2000-2003), this paper contains the outcome of a research on labour brokers in China. It will focus on the composition and functions of labour brokerage in today's restructuring processes of the labour market. The formal and informal dimensions and their impact will be particularly addressed. Furthermore, the institutionalization of the labour market will be discussed.
Keywords: 330; Personalberatung; Arbeitsmarkt; China